Corporate Social Responsibility Strategy in Maintaining Culinary Company Image Case Study of Waroeng Steak and Shake Purwokerto Branch - Sinaga, Risni; Warsito, Chandra (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Corporate Social Responsibility (CSR) is an action carried out by the company in accordance with the company's capabilities as a form of responsibility for the community and the environment around the company. The purpose of this research is to find out how the implementation of Corporate Social Responsibility in maintaining the company's image at Waroeng Steak And Shake Purwokerto Branch. This research is a field research with a qualitative descriptive approach. Data collection techniques using observation, interviews, and documentation. Meanwhile, data analysis was carried out by data reduction, presentation, and drawing conclusions. The technique of examining the data in this study used the triangulation method. Based on the results of the research conducted, it can be concluded that the implementation of the Corporate Social Responsibility program can maintain the Company's Image at Waroeng Steak And Shake Purwokerto Branch through the strategy of establishing communication and friendship.